Correlation of climate variation and NDVI values using Landsat scenes in the Amazonian penillanura of Yurimaguas - Peru, from 1984 to 2023 - Daniela Durand Poma, Milagros (2024)
Despite the decrease in deforestation rates in the world, it is still an expanding problem in tropical areas such as the Amazon, losing millions of hectares of forests per year, due to weak governance of their territories and driven mainly by agriculture, livestock and a strong expansion of agro-industrial plantations such as oil palm in recent decades. Therefore, it is necessary to know the extent of the impacts generated in the alteration of local climates and how they affect the surrounding populations and ecosystems. Therefore, the objective of the research is to analyze the impact of deforestation and changes in vegetation cover on the variation of temperatures and precipitation in the town of Yurimaguas - Peru, between 1984 and 2023. For this purpose, meteorological data were used to determine changes in the local climate and global warming, processed in Microsoft Excel software, as well as Landsat satellite images, processed in QGIS software, to see the evolution of the landscape by calculating the NDVI. The results show that the maximum and average NDVI of the study area have a negative trend, associated with the increase in temperatures of up to 2 °C in 40 years and the loss of 25% of its primary forests in the last 20 years, which means more than 2,200 hectares deforested in a single year. It is concluded that agroindustrial monocultures such as oil palm, together with other activities that change land use, have a strong impact by removing large tracts of native forests for decades, which is projected in the negative trend shown by the NDVI values, a phenomenon that is due to the greater effect of global warming on the local climate, the reduced water supply to ecosystems and increased levels of evapotranspiration, which affect the water balance of the soil and the vigor of its vegetation..